Acceleration of Ions in Jovian Plasmoids: Does Turbulence Play a Role?. Issue 7 (3rd July 2019) - Kronberg, E. A.; Grigorenko, E. E.; Malykhin, A.; Kozak, L.; Petrenko, B.; Vogt, M. F.; Roussos, E.; Kollmann, P.; Jackman, C. M.; Kasahara, S.; Malova, Kh. V.; Tao, C.; et al.
Abstract: The dissipation processes which transform electromagnetic energy into kinetic particle energy in space plasmas are still not fully understood. Of particular interest is the distribution of the dissipated energy among different species of charged particles. The Jovian magnetosphere is a unique laboratory to study this question because outflowing ions from the moon Io create a high diversity in ion species. In this work, we use multispecies ion observations and magnetic field measurements by the Galileo spacecraft. We limit our study to observations of plasmoids in the Jovian magnetotail, because there is strong ion acceleration in these structures. Our model predicts that electromagnetic turbulence in plasmoids plays an essential role in the acceleration of oxygen, sulfur, and hydrogen ions. The observations show a decrease of the oxygen and sulfur energy spectral index γ at ∼30 to ∼400 keV/nuc with the wave power indicating an energy transfer from electromagnetic waves to particles, in agreement with the model. The wave power threshold for effective acceleration is of the order of 10 nT 2 Hz −1, as in terrestrial plasmoids. However, this is not observed for hydrogen ions, implying that processes other than wave‐particle interaction are more important for the acceleration of these ions or that the time and energy resolution of the observations is too coarse. The results are expected to be confirmed by improved plasma measurements by the Juno spacecraft. Key Points: Ions are accelerated effectively by plasmoids in the Jovian magnetosphere Plasmoids with higher electromagnetic turbulence lead to stronger acceleration of oxygen and sulfur ions Acceleration of hydrogen ions is not correlated with wave power, possibly because of limitations in observations